Satellite remote sensing of coastal water quality in New Zealand - Mark P. Gall; Matthew H. Pinkerton; Tilmann Steinmetz; Simon Wood (New Zealand Journal of Marine and Freshwater Research, 2022)
Water quality in estuarine and coastal waters of Aotearoa New Zealand is of concern yet currently under‐monitored, reflecting challenges of sampling at regular intervals across large areas. Satellite products are currently underutilised (globally) by management agencies but could be part of a holistic approach. NIWA‐SCENZ (Seas, Coasts and Estuaries New Zealand) is a website providing access to MODIS‐Aqua products at moderate spatial resolution (500 m) across relatively clear coastal waters (Case 1) to turbid coastal waters (Case 2). It also provides advanced analytical tools on an extracted area of interest for trend assessment (Shiny‐SCENZ). For Case 1 areas product accuracy will be comparable to data from other websites using the same algorithms. For Case 2 and transition (blended) areas, although tuned to New Zealand conditions, accuracy of products requires validation. Data availability is mainly impacted by cloud cover, but also adjacency to land and bottom reflection. On average